Türkiye’de Yayınlanan Akademik Dergilerin Niteliklerindeki Zaman İçerisindeki Değişim Nedenleri: Sağlık, Sosyal ve Teknik Bilim Alanlarında Yayınlanan Dergiler Üzerine Bir İnceleme - Kozak, Nazmi (Bilgi Dünyası, 2003)
The present study was carried out by using data obtained out of the resulting databases of two data collection attempts concerning academic periodicals published in Turkey being namely those of 1997-1998 and 2002. The aim of this study was to investigate the changes during the last five years in scientific article evaluation, in applied standards and in other features of general context of academic periodicals focusing upon medical, social and technical sciences. It was concluded that Turkish academic periodicals indicated remarkable improvements in accordance with the fulfillment of expected criteria of academic promotion. It sems that the introduction of the same criteria should have imposed a positive effect in improving the quantity of scientific studies.